A CHARACTERIZATION OF THE U.S. RESIDENTIAL DECK MATERIAL MARKET. - SHOOK, STEVEN R. ; EASTIN, IVAN L.
CURRENT ESTIMATES INDICATE THAT OVER 6.5 MILLION DECKS ARE CONSTRUCTED ON U.S. RESIDENTIAL STRUCTURES ON AN ANNUAL BASIS AT A COST OF $1.9 TO #3 BILLION. OVER THE PAST DECADE, THE RESIDENTIAL DECK MATERIAL MARKET EXPERIENCED ROBUST EXPANSION, GROWING AT AN ANNUALIZED RATE OF 8.1 PERCENT BETWEEN 1991 AND 1999.....